2009
DOI: 10.1590/s0104-42302009000300027
|View full text |Cite
|
Sign up to set email alerts
|

Abortamento espontâneo e provocado: ansiedade, depressão e culpa

Abstract: ResumoObjetivOs. Caracterizar a população que sofreu abortamento; investigar a existência de ansiedade e depressão; verificar se existe ou não sentimento de culpa após o abortamento e comparar os resultados entre mulheres que sofreram abortamento espontâneo e as que provocaram-no. MétOdOs. 50 mulheres com abortamento espontâneo e 50 com provocado foram entrevistadas 30 dias após o abortamento. Foi realizada entrevista com questões abertas e fechadas e aplicada a escala Hospital Anxiety and depression. intROdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
21

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 14 publications
1
5
0
21
Order By: Relevance
“…From this perspective, the individual experience of abortion also brings a social meaning. As found in this study, a study conducted in Sao Paulo with women who have had abortions showed that all of them were faced with the pain and grief related to the impossibility of realizing motherhood 13 , which reinforces the idea that the meaning that is assigned to an experience varies according to the attitude at the time of reflection 10 . When assessing the care received, the woman says she has received some personalized attention and that the doctor who accompanied her from the prenatal could look after her in the process of abortion.…”
Section: Discussionsupporting
confidence: 76%
“…From this perspective, the individual experience of abortion also brings a social meaning. As found in this study, a study conducted in Sao Paulo with women who have had abortions showed that all of them were faced with the pain and grief related to the impossibility of realizing motherhood 13 , which reinforces the idea that the meaning that is assigned to an experience varies according to the attitude at the time of reflection 10 . When assessing the care received, the woman says she has received some personalized attention and that the doctor who accompanied her from the prenatal could look after her in the process of abortion.…”
Section: Discussionsupporting
confidence: 76%
“…Alguns trabalhos apontam que o aborto pode aumentar o risco de depressão (NOMURA; ALVES; ZUGAIB, 2011;BENUTE et al, 2009;REES;SABIA, 2007). Além disso, por ser crime no Brasil, o atendimento prestado às mulheres em abortamento muitas vezes é realizado de forma não qualificada, sem responder às necessidades da saúde mental ou física, sendo feito de forma impessoal, desrespeitosa, ou mesmo impregnada de julgamentos morais por parte da equipe de profissionais que prestam o atendimento (AQUINO et al, 2012;MOTTA, 2005;BRASIL, 2011).…”
Section: Discussão E Considerações Finaisunclassified
“…Legally, the solution to this problem can only be given by the weighting of the principle of proportionality (12) . The practice of abortion ends up introducing a conflict of morally established duty, which brings guilt to women from their individual decision not to opt for keeping the pregnancy, because the social expectation of motherhood is seen as a wonderful and ideal experience, and the mother must play her role to perfection (13) . Research has shown that the arguments for or against abortion have not favored women in order to mitigate the physical and/or emotional trauma arising from this experience, and health services have been identified as inept in this process (14) .…”
Section: Introductionmentioning
confidence: 99%